Bayesian hierarchical evaluation of dose-response for peanut allergy in clinical trial screening. (May 2021) - Haber, Lynne T.; Reichard, John F.; Henning, Alice K.; Dawson, Peter; Chinthrajah, R. Sharon; Sindher, Sayantani B.; Long, Andrew; Vincent, Melissa J.; Nadeau, Kari C.; Allen, Bruce C.
Abstract: Risk-based labeling based on the minimal eliciting doses (EDs) in sensitized populations is a potential replacement for precautionary allergen labeling of food allergens. We estimated the dose-response distribution for peanut allergen using data from double-blind placebo-controlled food challenges (DBPCFCs) conducted in the US at multiple sites, testing a population believed to be similar to the general U.S. food allergic population. Our final (placebo-adjusted) dataset included 548 challenges of 481 subjects. Bayesian hierarchical analysis facilitated model fitting, and accounted for variability associated with various levels of data organization. The data are best described using a complex hierarchical structure that accounts for inter-individual variability and variability across study locations or substudies. Bayesian model averaging could simultaneously consider the fit of multiple models, but the Weibull model dominated so strongly that model averaging was not needed. The ED01 and ED05 (and 95% credible intervals) are 0.052 (0.021, 0.13) and 0.49 (0.22, 0.97) mg peanut protein, respectively. Accounting for challenges with severe reactions at the LOAEL, by using the dose prior to the LOAEL as the new LOAEL, the ED01 drops to 0.029 (0.014, 0.074) mg peanut protein. Our results could aid in establishing improved food labeling guidelines in the management of food allergies. Highlights: Dose-response modeled for peanut DBPCFCs conducted using standardized protocols. The study population was US adults and children from multiple geographic locations. Repeated tests on the same individuals were moderately correlated, with some outliers. Bayesian hierarchical analysis addressed inter-individual variability. The calculated ED01 and ED05 were 0.052 and 0.49 mg peanut protein, respectively.